Asian‐specific vertical cup‐to‐disc ratio cut‐off for glaucoma screening: An evidence‐based recommendation from a multi‐ethnic Asian population. (20th August 2020) - Soh, Zhi Da; Chee, Miao Li; Thakur, Sahil; Tham, Yih Chung; Tao, Yijin; Lim, Zhi Wei; Mani, Baskaran; Wong, Tina T.; Aung, Tin; Cheng, Ching‐Yu
Abstract: Importance: Evidence‐based guidelines are essential for glaucoma screening to work effectively. Background: To derive a vertical cup‐to‐disc ratio (VCDR) cut‐off for glaucoma screening in a multi‐ethnic Asian population. Design: The Singapore Epidemiology of Eye Diseases (SEED) study is a population‐based study conducted from 2004 to 2011 in a single tertiary care research institute. Participants: SEED comprised of 10 033 Chinese, Malay and Indian adults aged ≥40 (response rate 75.6%). After excluding participants with a history of glaucoma medication or surgery, 9673 participants were included for analysis. Methods: A systematic eye examination, which included applanation tonometry, visual field testing, gonioscopy and dilated fundus examination was conducted. Main Outcome Measure: Diagnosis of glaucoma. Results: The distribution of VCDR and VCDR asymmetry were relatively homogenous in this multi‐ethnic Asian population, with a 97.5th percentile value of 0.67 and 0.17, respectively. In the absence of more definite signs of glaucoma, VCDR ≥0.60 and VCDR asymmetry ≥0.20 provided the best balance between sensitivity (95.1%) and specificity (90.9%) in detecting glaucoma. For larger optic disc (≥2.0 mm), VCDR ≥0.65 with VCDR asymmetry ≥0.20 provided the best balance between sensitivity (84.8%) and specificity (93.2%). Conclusion and relevance: Overall, VCDR ≥0.60 with VCDR ≥0.20 asymmetry provides a good balance between sensitivity and specificity in detecting glaucoma. For larger optic disc, VCDR ≥0.65 should be considered instead to mitigate against false‐referrals due to larger physiological disc cupping. Our findings may act as a reference to populations with similar VCDR distribution.